Nightmares do result in psychophysiological arousal: a multimeasure ambulatory assessment study - Paul, Franc; Alpers, Georg W.; Reinhard, Iris; Schredl, Michael (Psychophysiology, 2019)
Individuals who frequently experience nightmares report compromised sleep quality, poor daytime mood, and functioning. Previous research has aimed at linking these impairments with altered sleep architecture, but results were inconclusive. One plau-sible explanation is that only a few studies recorded markers of autonomic nervous system activity. For the first time, this study collected such markers under ecologi-cally valid conditions with ambulatory assessment. In 19 individuals with frequent nightmares (≥1 nightmare/week) and 19 healthy control participants (<1 nightmare/month), measures indicating autonomic activation (heart rate, heart rate variability, respiration cycle length, electrodermal fluctuations, EEG arousals, saliva cortisol, REM density) were collected while applying ambulatory polysomnographic assess-ment during 3 consecutive nights. When nightmare participants reported a night-mare, we analyzed the last 5 min of REM sleep before awakening and compared these data to their non‐nightmares as well as to the dream episodes of control participants [...]
First published 30 March 2019
Gesehen am 01.10.2019